Late Marx and the Russian Road : Marx and the Peripheries of Capitalism - Shanin, Teodor (Book collections on Project MUSE., 1983)
"The mid-part of the book is mainly given to the drafts of Marx's 1881 discussion concerning rural Russia and some supplementary materials ... The book's first part offers some interpretations of Marx's work at the last stage of its development, relating directly to the drafts published ... The final part three of the book presents some materials which come to trace the intellectual bridges between Marx's writings on Russia and the Russian revolutionary tradition."--Introduction